Jurisdição constitucional e precedentes vinculantes no Brasil - MAGALHÃES, Breno Baía (Universidade Federal do Pará, 2017)
The work provides some discussion regarding the binding effect, which aim to reconcile such institute within the practice of Brazilian judicial review, pointing out the importance of the constitutional interpretation made by the Supreme Court and the protection of fundamental rights. In said work, precedents are binding principles, which have gravitational force justified by the principle of equality in applying the law and the constitutional complaint is considered an important instrument for the interpretation of the binding precedent, capable of keeping the ways open for further distinguishing or reconsideration of prior decisions. Thus, the category that imposes the formal binding is the decision norm, which is a legal proposition able to sustain the ruling of the court on the (un) constitutionality of the act. We conclude that the refusal to give a broader transcendent binding effect indicates a strengthening of the diffuse control, allowing the interpretation and development of the precedents. Ronald Dworkin´s theory of law was chosen to support the conclusions of the study.